Gas gangrene after colonoscopy. Issue 903 (1st January 2001) - Jamieson, N F; Willoughby, C P
Abstract : A case of spontaneous clostridial myonecrosis developing shortly after diagnostic colonoscopy is described. The prime underlying factor proved to be an unsuspected colonic cancer, developing in a patient with pre-existing ulcerative colitis and sclerosing cholangitis.